Lyrics in Aespa’s “Life’s Too Short” and Olivia Rodrigo’s “Traitor” - Putri Anastasia Silalahi; Bernieke Anggita Ristia Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
This study performs a semantic analysis of the song lyrics from